Policy and strategy for quality improvement: a study on the Chittagong City Corporation, Bangladesh - Quddus, S. M. Abdul (2018)
Abstract: The overall policy and strategies of an organization i.e. employee policy or employee development strategies, resource management as well as monitoring and control strategies characteristically have an effect on the quality management of a particular organization. These policies usually also have impact on the stakeholders i.e. satisfaction of the wider community and employees of the particular organization. The aim of this paper is to examine the policy and strategies of the Chittagong City Corporation for quality improvement and how these policy and strategies impact on the needs of its stakeholders. This paper is guided by the EFQM model as the theoretical underpinning that provides specific enabler criteria of quality management of organizations such as employee policy, development of partnerships and resource management, and the monitoring of strategies of an organization. These enabler criteria help to explain the ways in which total quality management (TQM) is implemented in any organization (Legido-Quigley, 2008). Data for this study was collected from a total of 142 participants, including selective officials of the Chittagong City Corporation (CCC), city dwellers, government officials and civil society representatives by using a structured questionnaire. In relation to this study, both quantitative and qualitative data collection methods were used to gather and analyze information. The findings of this study thus reveal that the CCC has failed to convey clearly its quality mission and objectives to its employees at all levels. The CCC has also failed to spread its organizational quality goals to the city's residents since it has no effective mechanism to exchange views or engage in dialogue with them. In addition, different staffs have different understandings of the quality objectives of the organization. However there does indeed exist some systems for a sort of systematic assessment of organizational effectiveness, benchmarking techniques, self-assessment processes and information systems in the CCC to promote continuous improvement.